1972
DOI: 10.1042/bj1290743
|View full text |Cite
|
Sign up to set email alerts
|

The enzymic conversion of linoleic acid into 9-(nona-1′,3′-dienoxy)non-8-enoic acid, a novel unsaturated ether derivative isolated from homogenates of Solanum tuberosum tubers

Abstract: 1. A major component of the lipids in aqueous (pH7.5) homogenates of tuber tissue from Solanum tuberosum was isolated and characterized as 9-(nona-1',3'-dienoxy)non-8-enoic acid. 2. This novel unsaturated ether fatty acid derivative, which contains a butadienylvinyl ether function, has the structure: [Formula: see text] and is formed from linoleic acid by a sequence of enzymic reactions. 3. A precursor of the unsaturated ether derivative is 9-d-hydroperoxyoctadeca-10,12-dienoic acid, formed by the action of S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
57
0

Year Published

1979
1979
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(66 citation statements)
references
References 20 publications
9
57
0
Order By: Relevance
“…This feature distinguishes this enzyme from other c loned DES enzymes from Solanaceae species. The conversion of LA into the divinyl ether CA was first reported in the early 1970s by Galliard and co-workers [20]. Related activities leading to formation of EA and EnA are known from garlic and different Ranunculaceae species and a number of algae [9][10][11].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This feature distinguishes this enzyme from other c loned DES enzymes from Solanaceae species. The conversion of LA into the divinyl ether CA was first reported in the early 1970s by Galliard and co-workers [20]. Related activities leading to formation of EA and EnA are known from garlic and different Ranunculaceae species and a number of algae [9][10][11].…”
Section: Discussionmentioning
confidence: 92%
“…The fixation was performed at 4 °C for 12 h. After three washes for 20 min each in PBS the specimens were dehydrated in a graded ethanol series (20, 30, 40, 50, 60, 70, 90, 97, 100 % ethanol), each step for 40 min. Embedding in Steedman's wax (Vitha et al, 1997) was done first for 1 h in 100 % ethanol, then in a graded wax/ethanol series (10,20,35,50,65, and 80 % v/v wax) at 37 -40 °C followed by three changes of pure wax, each for 1 -2 h. Ribbons of 8 µm thick sections were placed on silanized slides coated with egg white and stretched by addition of a small drop of distilled water to one end of the ribbon. The excess water was soaked away from the opposite end of the ribbon by filter paper.…”
Section: Immunocytochemistrymentioning
confidence: 99%
“…Labeling studies with [1,2-13 C 2 ]acetate showed a contiguous series of nine intact acetate units terminated by a methyl-derived acetate carbon at C-1 of 9D. A Hock rearrangement similar to that involved in divinyl ether synthesis [168], has been proposed that is initiated from a 6-hydroperoxide species and followed by an allene-acetylene isomerization cumulatively attaching the oxygen atom to the acetylenic ether and fracturing the unsaturated chain.…”
Section: α-Oxidation-while α-Oxidationmentioning
confidence: 99%
“…1) is one of the non-common routes of the plant lipoxygenase pathway. This route was discovered by Galliard and his colleagues in potato tubers [3][4][5][6]. Divinyl ether synthase from potato utilises specifically 9-HPOD and 9-HPOT.…”
Section: Introductionmentioning
confidence: 99%